Breaking barriers of access to land for women - Mukasa, Hellen; Reynier, Aurélie; Ogunsumi, Lucia (Technical Centre for Agricultural and Rural Cooperation, 2019)
This brief looks at the role formal and traditional legal systems in determining women’s access to land and other productive resources and recommends some policy reforms to strengthen the position of women in agriculture and agribusiness.